Husband's Support, Anxiety and Maternal-Fetal Attachment in Pregnant Women: a Scoping Review - Yuni Purwati; Noor Pramono; Mohammad Hakimi; Anggorowati Anggorowati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
MFA is an emotional bond that develops between mother and fetus. Maternal-fetal attachment is based on cognitive representations such as thoughts, feelings, and behaviors representing a pregnant mother's affection for her fetus. Husband's support and anxiety are factors that influence the quality of MFA and birth outcomes. Objective: to analyze husband's support, anxiety level and MFA level. Method: Scoping review using the PRISMA Scr framework. Using the PICO Framework, the search strategy was searched using keywords in the Scopus, Ebsco, Pubmed, ScienceDirect and Proquest databases. Critical Assessment is done with JBI. Results: 14 articles were obtained that were screened using the PRISMA ScR framework, 50% came from developing countries and 50% from developed countries. Articles with cross-sectional research methods, cohort and longitudinal studies each 28.6% and case control studies 14.2%. JBI results from 14 articles resulted in a score of more than 50% so it was accepted. Conclusion: MFA is influenced by husband's support and anxiety which impacts birth outcomes and infant development. Efforts are needed to increase MFA through MFA training for pregnant women and constructive anxiety management.